一种三苯胺衍生物及其制备方法、光致变色薄膜材料及其制备方法和应用 (2025)
本专利申请公开了一种三苯胺衍生物及其制备方法、光致变色薄膜材料及其制备方法和其应用。本专利申请以三苯胺基团作为给体结构，以连接不同受体基团R，通过Suzuki反应合成了客体材料，而主体材料为聚甲基丙烯酸甲酯(PMMA)。通过主客体掺杂的方法可以得到具有光致变色现象的光刺激响应薄膜材料，在经365nm的紫外灯照射前后表现出不同的发光颜色。此种在光照下可以发生发光变色的薄膜材料可应用于显示、信息加密、防伪等方面。此种制备方法简单易操作，为制备光致变色发光材料提供了一种新的设计思路。 The invention discloses a triphenylamine derivative, a preparation method of the triphenylamine derivative, a photochromic thin film material, a preparation method of the photochromic thin film material and application of the photochromic thin film material. According to the invention, a triphenylamine group is used as a donor structure to connect different acceptor groups R, a guest material is synthesized through a Suzuki reaction, and a host material is polymethyl methacrylate (PMMA). The photostimulus response thin film material with a photochromic phenomenon can be obtained through a subject-object doping method, and the photostimulus response thin film material shows different luminescence colors before and after being irradiated by a 365nm ultraviolet lamp. The thi